Environmental Impact and Life Cycle Costs of Large-Scale Hydroelectric Power Plants - Nur, A Ida Nurfaida; Sasongko, Nugroho Adi; Boedoyo, M Sidik (CV. Rayyan Dwi Bharata, 2024)
Utilization of water resources as a renewable primary energy source can be utilized synergistically for many benefits. Hydroelectric power is a renewable energy source with large reserves in Indonesia. In principle, all development activities have environmental impacts in the form of positive (beneficial) impacts and negative (harmful) impacts, so an analysis of environmental impacts and life cycle costs is needed. This paper aims to analyze the environmental impacts and life cycle costs of hydroelectric power plants using the literature review method to reach conclusions regarding the possible environmental impacts and life cycle costs required for a hydroelectric power plant. Interactions between hydroelectric project locations and environmental areas suggest that hydroelectric project construction may adversely impact certain important habitats, and impacts may worsen in the future. By planning life cycle costs before a hydroelectric power plant is installed, the costs that will be incurred will be focused.